Vivências no cotidiano da sala de aula: atitudes da professora que contribuem para a predominância de estados emocionais de bem-estar nos alunos - Vasconcellos, Mariana Pires de (2024)
The purpose of the research was to identify the teacher’s attitudes that contribute to the predominance of emotional states of well-being in students and in herself, leading to a good interaction in the classroom, aiming at the quality of the learning process. The context was the classroom where the researcher works as a teacher in a private school in São Paulo. There were 32 students in this 2nd grade in Elementary school class. The fieldwork occurred in two stages: students’ production through drawings and captions in the first semester of 2023, and observation of daily scenes of the classroom context in the second semester of 2023. For the students’ production, there were guidelines such as: what the children liked the most during the week at school and in the classroom; what they would like to do the following week at school and in the classroom; what they liked the most about what happened in the classroom during the past week; writing down something they would like to have in the classroom every day; what they mostly enjoyed during the semester at school and what they would like to do the following semester (after the school break in July) at school; and, when they return from the vacation, what they would like to do in that current semester at school. The selection of daily scenes was in line with the research goals. The theoretical framework used both to understand the concept of human development, education and affectivity and to analyze and discuss the results, was the psychogenetics of Henri Wallon and researchers of his work. This research falls under qualitative studies in education. Remarks were made by the teacher-researcher to analyse and discuss the results in addition to the instruments used to produce the information. It was found that listening to and welcoming the students, promoting and allowing self-expression, recognizing and dealing with emotions and feelings, as well as respecting the student as an individual, are conditions that contribute to the predominance of emotional states of well-being in them and in the teacher, leading to good coexistence in the classroom and promoting the quality of the learning process. Additionally, it became clear that play, movement and interpersonal relationships are situations that children enjoy the most in school, that mathematics is the curricular component they are most interested in and that teaching practices that involve the active participation of students, varied and playful challenges, group practices and the use of various school spaces to carry out activities are essential elements to be considered in the classroom routine